The contribution of corporate social responsibility to the sustainability of small and medium-sized enterprises: A systematic review - Lopera, Natalia Andrea Lopera; Angarita, Ruby Sareth Joya; Cañas, Yuly Andrea Florez; Lievano, Jhony Alexander Barrera (Edelweiss Applied Science and Technology, 2025)
This article analyzes how Corporate Social Responsibility (CSR) impacts small and medium-sized enterprises (SMEs) and the challenges they face in its implementation. It also explores the foundations of CSR and its link to sustainability through a systematic review covering publications from 2005 to 2023, which allowed for the identification of areas of influence, integration difficulties, and financial limitations, as well as competitive disadvantages and market positioning. Furthermore, the bibliometric analysis reveals an increase in CSR research, highlighting quantitative methodology as the most applied (54.74%) and surveys as the primary data collection tool (53.68%). In turn, it is evident that CSR significantly contributes to improvements in competitiveness (12.63%), sustainability (50.53%), and corporate image (7.4%). It concludes that implementing CSR in business models promotes sustainable and ethical practices that benefit companies and their relationships with modern consumers, the environment, society, and innovation in management processes, technologies, areas of action, and interaction with stakeholders.